EFEKTIVITAS MODEL TUTOR SEBAYA DALAM MENINGKATKAN MAHARAH QIRA'AH: TINJAUAN LITERATUR SISTEMATIS - Fauziah, Asti; Kesuma, Guntur Cahaya; Farhan, Ali; Nur, Robiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The peer tutoring cooperative learning model has been widely applied to enhance reading skills (maharah qira'ah) in Arabic language education. This study aims to evaluate the effectiveness, challenges, and opportunities of this model through a systematic literature review. Data were collected from 12 journal articles published between 2020 and 2024, analyzed using a thematic synthesis approach. The results reveal that peer tutoring significantly improves students’ reading fluency, pronunciation accuracy, and text comprehension. These improvements are influenced by active interactions between tutors and students, as well as a supportive learning environment. However, challenges such as difficulty in selecting competent tutors and unbalanced group dynamics remain significant barriers to implementation. Additionally, the study found that students involved in peer tutoring demonstrated higher learning motivation compared to those in conventional methods. The novelty of this research lies in its focus on elementary education (madrasah ibtidaiyah) and oral reading skills (qiroah jahriyah), which are rarely explored in previous studies. This study concludes that peer tutoring is an effective strategy to enhance students’ maharah qira'ah, particularly at the elementary level. Recommendations are provided for developing more structured tutor training and integrating technology to support this model in the future.